Are symptoms after a colorectal segmental resection in deep endometriosis really improved? The point of view of women before and after surgery. (2nd October 2018) - Garavaglia, Elisabetta; Inversetti, Annalisa; Ferrari, Stefano; De Nardi, Paola; Candiani, Massimo
Abstract: Introduction: Bowel endometriosis can cause debilitating symptoms. Surgical colorectal resection is often required for symptomatic relief. Aim of our study was to evaluate quality of life over a one-year follow-up period in patients submitted to a colorectal resection for the treatment of deep endometriosis. Change in intestinal and extra-intestinal symptoms, and reproductive outcome were also evaluated. Methods: A prospective observational study was conducted on a cohort of 20 women affected by intestinal endometriosis and submitted to a laparoscopic colorectal resection. The subjects completed a questionnaire about quality of life (SF-36), and they scored in a 100-point rank questionnaire gynecological, urinary and gastrointestinal symptoms, pre-operatively and one- year postoperatively. Results: Significant improvements were observed in all domains of the SF-36 throughout the study period. Dysmenorrhea, dyspareunia and not menstrual pelvic pain showed a significant decrease 1 year after surgery. There was also a decrease in abdominal pain, rectal bleeding and constipation but not of nausea, abdominal pain, defecation pain, tenesmus, diarrhea, mucorrhea. Also some urinary symptoms did not improve. Conclusions: The radical surgical approach has a positive impact on quality of life, although it does not improve all the symptoms complained before surgery. Clear pre-surgical counseling and careful patient selection is suggested.